Raised Plasma Neurofilament Light Protein Levels Are Associated with Abnormal MRI Outcomes in Newborns Undergoing Therapeutic Hypothermia - Shah, Divyen K.; Ponnusamy, Vennila; Evanson, Jane; Kapellou, Olga; Ekitzidou, Georgia; Gupta, Neelam; Clarke, Paul; Michael-Titus, Adina T.; Yip, Ping K. (Frontiers in Neurology, 2018)
Aims and Hypothesis: Hypoxic-ischaemic encephalopathy (HIE) remains an important cause of death and disability in newborns. Mild therapeutic hypothermia (TH) is safe and effective, however there are no tissue biomarkers available at the bedside to select babies for treatment. Aims: To show that it is feasible to study plasma neurofilament light (NfL) levels from newborns and to evaluate their temporal course. Hypothesis: raised plasma NfL protein levels from newborns who undergo TH after HIE are associated with abnormal MRI outcomes. Methods: Between February 2014 to January 2016, term newborns with HIE treated with TH for 72 hours had plasma samples taken at three time points: (i) after the infant had reached target temperature, (ii) prior to commencing rewarming and (iii) after completing rewarming. Infants with mild HIE who did not receive TH had a single specimen taken. NfL protein was analyzed using an enzyme-linked immunosorbent assay. Results: Twenty-six newborns with moderate-severe HIE treated with TH were studied. Half of these had cerebral MRI predictive of an unfavorable outcome. Plasma NfL levels were significantly higher in the TH group with unfavorable outcome (median age 18 hours) compared to levels from both the mild HIE group and TH group with favorable outcome (F=25.83, p<0.0001). Newborns who had MRIs predictive of unfavorable outcome had significantly higher NfL levels compared to those with favourable outcomes, at all three time points (mixed models, F=27.63, p<0.001). A cut-off NfL level >29 pg/mL at 24 hours is predictive of an unfavorable outcome (sensitivity 77%, specificity 69%, PPV 67%, NPV 72%) with increasing predictive value until after rewarming (sensitivity 92%, specificity 92%, PPV 92%, NPV). Interpretation of Research: Plasma NfL protein levels may be a useful biomarker of unfavorable MRI outcomes in newborns with moderate-severe HIE and may assist in selecting newborns for adjunctive neuroprotective interventions. Larger studies with NfL testing at earlier time points are required.